Optimalisasi Organisasi Kantor dalam Lembaga Dakwah Sosial: Analisis Model dan Pola Berbasis Manajemen Perkantoran Modern - Subekti; Ngatiyah; Slamet Riyadi; Dewi Ratnawati; Ade Titie Solihati; Sahrullah; Meity Suryandari (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This article comprehensively discusses the integration of office organization principles within the unique context of social da'wah institutions, with the primary goal of enhancing operational efficiency and organizational sustainability. This study employs a conceptual qualitative approach to conduct an in-depth analysis of the characteristics of the most relevant and effective models, forms, and patterns of office organization when applied in a typical da'wah environment. The findings indicate that the categorization of office organization in da'wah institutions can be effectively grouped based on three main dimensions: structural, functional, and organizational culture. Furthermore, the implementation of a holistic workplace management model, along with the adoption of flexible organizational patterns such as adhocracy and clan culture, has been empirically proven to significantly support the optimization of resource utilization and the more sustainable achievement of da'wah objectives. This article also specifically emphasizes the importance of technological adaptation and strategic management approaches in addressing increasingly complex global challenges.